Influence of reinforcement arrangement details on mechanical behavior of precast concrete barrier with loop connection. (October 2020) - Basit, S.; Maki, T.; Mutsuyoshi, H.; Ishihara, Y.; Tajima, H.
Abstract: Concrete bridge barriers are installed as road safety facilities to prevent vehicles or pedestrians on the road from exiting the lane or entering the opposing lane. Deterioration due to the aging of reinforced concrete members, vehicle crashes, and renovation/extension of bridges necessitate the repair and reinstallation of barriers. A precast concrete barrier solution is used to replace old deteriorated barriers to enable fast and effective completion of structures. This precast barrier is connected to a highly durable cementitious mortar injected into the loop rebar connection. This research shows that a beam specimen can be utilized to understand the detailed behavior of the connection. The results of the experimental study indicate that the configuration of the loop reinforcement provides excellent anchoring capacity and a failure mode that is more stable and capable of greater energy absorption than the existing system. It is revealed that the cracking pattern and mechanical behavior of the reinforcement are highly influenced by the re-arrangement of the reinforcement in the connection. The reinforcement congestion and stress concentration at the edge can be resolved safely by the details proposed in this study, and it can be used effectively for the design of impact loading conditions. The outcomes of this work will lead to important design guidelines for the connection of precast concrete barriers with deck slabs.